Understanding the Impact of Employee Investigations on Those Who Lead Them: A Case Study from NHS Wales - Andrew Jonathan Cooper; Doris Anita Behrens; Sophie Elizabeth Jones; Adrian Neal; Aled Jones; Walter Hyll (Administrative Sciences)
In healthcare, there is growing awareness of the potential harm that disciplinary processes can have on employees, service delivery, and organizational culture. However, little attention has been given to the impact on those responsible for conducting these investigations. This study examines investigator harm through a cross-sectional survey, simultaneously collecting qualitative and quantitative data from 71 participants across 10 NHS Wales organizations. The findings indicate that investigators experience harm when conducting employee investigations. While those with more experience perceive themselves as better prepared to follow the formal steps of the disciplinary policy and process, their ability to prevent harm to themselves or others remains unchanged. Additionally, more experienced investigators are not more aware of their organization’s well-being priorities or strategies for mitigating harm. These findings highlight the need for greater support for investigators, including coaching and post-investigation debriefing. Training should raise awareness of the impact of employee investigations on all stakeholders and the importance of applying disciplinary policy and processes empathically. Finally, policies and processes should acknowledge the harm they may cause and explicitly provide strategies for harm reduction, such as treating formal investigations as a measure of ‘last resort’.